Recuperação de turbinas hidráulicas danificadas por erosão cavitacional por soldagem com aço inoxidável/cobalto - Macedo, Ricardo Vechin de [UNESP] (2014)
In the current energy scenario, it becomes increasingly imperative to produce energy more efficiently. Thus, the gain in efficiency through processes that allow a greater time between maintenance, also generates a reduction in costs for the production of energy. However, a major problem faced by hydropower plants, is the phenomenon of cavitation, which generates as a result of erosion turbine parts, with loss of material and performance. Studies indicate as to minimize this situation, a better hydrodynamic design of the turbines and the use of materials noblest and resistant to cavitation erosion. In the new turbines, design improvement and the use of noble materials such as ASTM A743 Gr CA6-MN, reduce the effects of cavitation and prolong the need for recovery of machinery. However, to mitigate these effects in turbines that are already in operation, especially with more than 30 years, is necessary the application of coatings with features that enable mitigation of this phenomenon. In that sense, occurred the development of austenitic alloys with cobalt, which due to operational difficulties that existing at the time, initially proved ineffective for increasing the resistance against cavitation and the intervals between recoveries. To ensure the operability of these alloys was developed in 2000 by LABSOLDA, MIG / MAG welding with thermal pulse, or bi-pulsed, which provided, along with hydroelectric plants, one popularization of this alloy in the recovery of cavitation erosion and an effective improvement cavitation resistance of coated areas of hydraulic turbines, the effect of reducing the period of arrest and deposition of material. However, in the last 10 years, significant developments in conventional soldering machines, including the incorporation of electronic controls welding, which also reduces interference welder during welding. In this study, a comparison was made of an stainless steel ...